Prevalence and clinical features of anxiety disorders: Tunisian study about 436 subjects. (1st June 2022) - Jabeur, M.; Gassab, L.; Ayadi, A.; Ben Mohamed, B.; Zaafrane, F.; Gaha, L.
Abstract : Introduction: Anxiety disorders represent one of the most common mental disorders following a chronic course. Objectives: The aim of our study is to determine the prevalence, incidence and clinical characteristics of these disorders. Methods: We conducted a retrospective and descriptive study about 436 outpatients fulfilling the DSM-V diagnostic criteria for anxiety disorder and followed in the department of psychiatry of Monastir (Tunisia) between 1998 and 2017. Selective mutism and separation anxiety were excluded for lack of cases. Results: The overall prevalence was 5.51%. Panic Disorder was the most prevalent anxiety disorder subtype (3.2%). The incidence of anxiety disorders in the last years has increased from 3.31% in 1998 to 7.5% in 2017. The mean age at diagnosis was 37.76±12.87 years [16-77]. Female gender was the most prevalent in overall anxiety disorders with a sex ratio of 0.78, however, a significant male predominance was recorded in Social Anxiety Disorder (SAD) with a sex ratio of 1.85. Generalized Anxiety Disorder patients were more likely to have low educational level (OR= 1.879), to be laborers (OR=2.55), to be married (OR=2.418) and to have children (OR=2.564) whereas SAD patients were more likely to have higher education (OR=9.118), to be students (OR=5.565), to be single (OR=11.325) and have no children (OR=7.464). Conclusions: This study highlignts the frequency of anxiety disorders and the fact that being a middle-age married woman with kids make oneself more prone to have an anxiety disorder. Specific attention should be paid to these anxiety disorders with early preventive programs. Disclosure: No significant relationships.